Cinematographic observation of the deformation of an antibubble when a spark-induced cavitation bubble oscillates in its vicinity - Bai, Lichun; Yan, Jiuchun; bai, Lixin; Zeng, Zhijie; ma, yuhang (Colloids and surfaces. A, Physicochemical and engineering aspects, 2020)
Deformation of an antibubble under the impact of a cavitation bubble. The non-uniformity of the thickness of the gas film strongly influences the rupture process of the antibubble. The dynamics of antibubble deformation under the impact of primary shock wave and secondary shock wave induced by the growth and collapse of cavitation bubble is analysed. [Display omitted] An antibubble is the opposite of a soap bubble: a thin spherical gas shell containing liquid inside and surrounded by liquid outside. The dynamic behaviour of antibubbles when a spark-induced cavitation bubble oscillates in their vicinity is studied using a high-speed video camera. It is found that the rupture process of antibubble impacted by shock wave is different from that of antibubble due to aging or puncture. There is a stable phase relationship between the cavitation bubble deformation and the antibubble deformation. The non-uniformity of the thickness of the gas film strongly influences the rupture process of the antibubble. The antibubbles will split horizontally into two parts, and the gas in the gas film of antibubbles will move and gather to the point where the air film is thickest, and then divide into two gas bubbles. The dynamics of antibubble deformation under the impact of primary shock wave and secondary shock wave induced by the growth and collapse of cavitation bubble is analysed.